Dampak ekspor ke Jepang dan investasi asing terhadap pendapatan perkapita masyarakat di Indonesia - Candra Mustika; Erni Achmad; Etik Umiyati (Jurnal Paradigma Ekonomika, 2018)
This study aims to analyze the development of exports to Japan and foreign direct investment and per capita income in Indonesia during the period 1993-2014 also the impact of exports to Japan and foreign direct investment on per capita income of Indonesian people in that period. During research period starting in 1993-2014 where the GDP per capita has fluctuated where the average value is 15.058 in thousand rupiahs per year with an average growth of 16.61%, then the results obtained during that period the highest growth in 1998 is 50.50% and the lowest growth occurred in 2012 which was 8.46%. FDI Indonesia has fluctuated with an average value of 17,804.61 million US dollars and with an average growth of 15.35%. From the regression results on both models, the results found that in the first model the value of exports to Japan has a positive and significant effect on GDP per capita while the FDI variable does not have a positive and significant effect on GDP per capita